You Cannot Judge an Argument by its Closure - Cohen, Daniel H. (Informal Logic)

(untitled) (Informal Logic, 2022)
The best arguments are distinguished by more than logical validity, successful rhetorical persuasion, or satisfactory dialectical closure. Argument appraisal has to look beyond the premises, inferences, and conclusions; it must consider more than just the objections and replies, and resolutions that satisfy the arguers might not satisfy outside critics. Arguers and their contexts can be important factors for assessing arguments. This conclusion is reached by considering several scenarios in which similar arguments—up to and including complete word-for-word identity—merit different critical responses.